Comparative study of presurgical skin infiltration depth measurements of melanocytic lesions with OCT and high frequency ultrasound. Issue 6 (23rd December 2016) - Varkentin, Arthur; Mazurenka, Mikhail; Blumenröther, Elias; Meinhardt‐Wollweber, Merve; Rahlves, Maik; Broekaert, Sigrid M. C.; Schäd‐Trcka, Susanne; Emmertinst, Steffen; Morgner, Uwe; Roth, Bernhard
Abstract : A reliable, fast, and non‐invasive determination of melanoma thickness in vivo is highly desirable for clinical dermatology as it may facilitate the identification of surgical melanoma margins, determine if a sentinel node biopsy should be performed or not, and reduce the number of surgical interventions for patients. In this work, optical coherence tomography (OCT) and high frequency ultrasound (HFUS) are evaluated for quantitative in vivo preoperative assessment of the skin infiltration depth of melanocytic tissue. Both methods allow non‐invasive imaging of skin at similar axial resolution. Comparison with the Breslow lesion thickness obtained from histopathology revealed that OCT is slightly more precise in terms of thickness determination while HFUS has better contrast. The latter does not require image post‐processing, as necessary for the OCT images. The findings of our pilot study suggest that non‐invasive OCT and HFUS are able to determine the infiltration depth of lesions like melanocytic nevi or melanomas preoperatively and in vivo with a precision comparable to invasive histopathology measurements on skin biopsies. In future, to further strengthen our findings a statistically significant study comprising a larger amount of data is required which will be conducted in an extended clinical study in the next step.Comparison of optical coherence tomography and high frequency ultrasound B‐Scans and a H&E stained histology of a melanocytic nevus. Abstract : Malignant melanoma is the most dangerous skin cancer type. A very important criteria for risk evaluation is the skin infiltration depth of the melanoma. Non‐invasive preoperative in vivo thickness assessment can provide additional information for histopathologists and has the potential to decrease false positive cases and avoid different steps of surgical intervention. With optical coherence tomography as well as high frequency ultrasound such thickness assessment is possible.